Italian readers of Ovid from the origins to Petrarch : responding to a versatile muse - Van Peteghem, Julie (Medieval and Renaissance authors and texts, 2020)
"The Latin poet Ovid continues to fascinate readers today. In Italian Readers of Ovid from the Origins to Petrarch, Julie Van Peteghem examines what drew medieval Italian writers to the Latin poet's works, characters, and themes. While accounts of Ovid's influence in Italy often start with Dante's Divine Comedy, this book shows that mentions of Ovid are found in some of the earliest poems written in Italian, and remain a constant feature of Italian poetry over time. By situating the poetry of the Sicilians, Dante, Cino da Pistoia, and Petrarch within the rich and diverse history of reading, translating, and adapting Ovid's works, Van Peteghem offers a novel account of the reception of Ovid in thirteenth- and fourteenth-century Italy"--